Improving Indoor Air Quality for Poor Families : A Controlled Experiment in Bangladesh - Dasgupta, S. (2012)
The World Health Organization's 2004 Global and Regional Burden of Disease Report estimates that acute respiratory infections from indoor air pollution (pollution from burning wood, animal dung, and other bio-fuels) kill a million children annually in developing countries, inflicting a particularly heavy toll on poor families in South Asia and Africa. This paper reports on an experiment that studied the use of different fuels in conjunction with different combinations of construction materials, space configurations, cooking locations, and household ventilation practices (use of doors and windows) as potentially-important determinants of indoor air pollution. Results from controlled experiments in Bangladesh were analyzed to test whether changes in these determinants can have significant effects on indoor air pollution. Analysis of the data shows, for example, that pollution from the cooking area is transported into living spaces rapidly and completely. Furthermore, it is important to factor in the interaction between outdoor and indoor air pollution. Hence, the optimal cooking location should take 'seasonality' in account. Among fuels, seasonal conditions seem to affect the relative severity of pollution from wood, dung, and other biomass fuels. However, there is no ambiguity about their collective impact. All are far dirtier than clean (LPG and Kerosene) fuels. The analysis concludes that if cooking with clean fuels is not possible, then building the kitchen with permeable construction material and providing proper ventilation in cooking areas will yield a better indoor health environment. PRACTICAL IMPLICATIONS: Several village-level measures could significantly reduce IAP exposure in Bangladesh. All would require arrangements and the assert of male heads-of-household: negotiated bulk purchases of higher cost, cleaner fuels; purchase of more fuel-efficient stoves; peripheral location of cooking facilities; building the kitchen with permeable construction material; rotation of women in cooking roles, to reduce their exposure; and ventilation of smoke through a stack tall enough to disperse smoke over a relatively broad area. It is expected that village men and women will agree to these measures if they become convinced that IAP poses a serious risk to health, and their actions will significantly reduce the risk. The keys to success are effective public education about the sources and risks of IAP, and financial and technical assistance for changes in cooking arrangements.